Design of A Website-Based Internship Information System (Case Study of Industrial Engineering UPN “Veteran” East Java) - Kartikasari, Bintang Andita; Donoriyanto, Dwi Sukma (AI Society & STMIK Indonesia, 2023)
The Industrial Engineering Study Program is one of the study programs at the Faculty of Engineering, UPN